Exploration of Islamic Religious Education Teaching Material Management in Higher Education - Nasrudin, Ega; Anwar, Saepul; Suresman, Edi (Institut Agama Islam Negeri Imam Bonjol Padang, 2026)
This study aims to examine how Islamic teaching materials are developed and managed at Telkom University, with a particular focus on integrating the values of sustainable development into the curriculum. The research seeks to understand how these materials are designed to remain relevant to learning outcomes while responding to contemporary global challenges. The study employs a qualitative approach. Data were collected through interviews with lecturers and academic managers, direct observations of the learning process, and analysis of institutional documents related to curriculum and teaching material development. This approach allows for an in-depth understanding of both the process and the context of material development. The results show that Islamic teaching materials are systematically designed in accordance with learning outcomes and incorporate key dimensions of sustainable development, including economic growth, social inclusion, and environmental protection. The development process emphasizes collaboration and deliberation through structured discussions before each semester, ensuring that the materials remain relevant to regulations and current social issues. In conclusion, a collaborative and sustainability-oriented model of teaching material development enhance the relevance of higher education and supports student engagement and achievement.